Keynote Address to the International Seminar on Malik Bennabi - Anwar Ibrahim (International Institute of Islamic Thought, 1992)
The dominant theme me comes across in Bennabi’s writings is how essential it is to cultivate ideas. He argued that proficiency and efficacy in nurturing ideas is a vital sign of intellectual and cultural development. In elaborating the role of ideas in the development of civilization, he went to the extent of saying that a civilization ptospers only by the depth of its guiding ideas. I am in accord with Shaykh Diraz of al Azhar when, writing in his preface to Bennabi’s book The Qur’anic Phenomena, he praised him for the =titude of his judgment, the zeal of his conviction, the precision of his terminology, and the beauty of his style. Apart from their profound intellectual implications, the pronouncements of Bennabi caw deep personal meanings for me. These attributes of Bennabi’s writings make him one of the most erudite intellectuals of the Muslim world. Moreover, what I discern in these attributes is that they rightly portray him in his totality. To me he is not an intellectual or a recluse, simply captivated by the bliss of his own awakening and without an organic link with his faith. Most assuredly, his pen symbolizes his faith, his convictions, and his ideological strategy. More than anything else, it serves as a constant reminder of the inevitability of the inner struggle for both personal and collective evolution. Civilizations do not become great, acquire power, or wane by some mysterious flux of nature. A civilization is the translation of ideas into intellectual capacity and material means to organize one’s environment. Ideas make the practice of power possible. Ideas devise the practical tools for living in the world. And ideas question whether we have attained our goal or failed our potential. Bennabi tells us that those who do not have the moral courage to grasp the guiding ideas of their civilization have not only the repetition of history but their irrelevance to the mamh of time as their future. The Qur’an, the raison d’etre of the ummah, is not a mere invitation; it is the imperative to think and ...